2011
DOI: 10.4317/medoral.16.e365
|View full text |Cite
|
Sign up to set email alerts
|

Marginal bone loss in relation to the implant neck surface: An update

Abstract: A review is made of the publications on the marginal bone loss of implants with a polished neck, rough neck with microthreading, and rough neck without microthreading. A PubMed search was carried out with the following key words: machined neck implant, polished neck implant, marginal bone loss, covering the period between January 1998 and March 2009. Inclusion was limited to those human clinical studies involving a minimum follow-up of 12 months, and registering the level of bone loss from the time of placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…It is a fact that bone-to-implant contact will not be the same in the palatine zone as in the buccal zone, as less contact is pro-duced on the buccal side this being a finer bone wall (10). Most of the research referenced in the present study only evaluate BIC in palatine areas, producing sets of values that are not altogether certain; generating averages based on this data alone assumes that BIC percentages will be the same all over the implant surface when this clearly not the case.…”
Section: Discussionmentioning
confidence: 99%
“…It is a fact that bone-to-implant contact will not be the same in the palatine zone as in the buccal zone, as less contact is pro-duced on the buccal side this being a finer bone wall (10). Most of the research referenced in the present study only evaluate BIC in palatine areas, producing sets of values that are not altogether certain; generating averages based on this data alone assumes that BIC percentages will be the same all over the implant surface when this clearly not the case.…”
Section: Discussionmentioning
confidence: 99%
“…This encompassed 15 reviews (Al‐Zahrani ; Aloy‐Prosper et al. ; Atieh et al. ; Attard and Zarb ; Baig and Rajan ; Blanes ; Cordaro et al.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that patient habits (Galindo-Moreno et al 2005), implant/ abutment design (Canullo et al 2010;Aloy-Prosper et al 2011;Penarrocha-Diago et al 2013; Monje et al 2014), prosthetic considerations (Cardaropoli et al 2006), bone substratum (Galindo-Moreno et al 2013b), and surgical aspects influence the MBL at 1 year of loading (Esposito et al 2009). It has also been found that initial bone resorption, considered to be physiological (Tatarakis et al 2012), occurs after the implants are functionally loaded (Hermann et al 2000a,b).…”
mentioning
confidence: 99%